A Fossa Canina Abscess Originated From First Maxillary Primary Molar: A Case Report Management - Rochim, Abdul (Insisiva Dental Journal, 2012)
A possible complication of fossa canina infections is reactive thrombosis of the vena angularis, which can lead to cavernous sinus phlebothrombosis. According to the literature there are different opinions about the treatment protocol of fossa canina abscesses. This study reports theunusual case of odontogenic infection in children. A four years old girl patient arrived at a dental clinic with her mother and sister. The patient presented with massive swelling and redness in the region of left eye. According to the subjective data obtained from her mother and sister, the swelling occurs in the morning, six hours before being taken to the dentist. We suspect that the left maxillary first primary molar caused the case. Management of this case is open bur and there was bleeding from the pulp without pain. After 4 min, swelling in the lower eyelid decreased. The condition is getting better after 39 min before the patient took the drug. The patient still get medicine for healing efforts.